Investigations into the impact of hearing loss and hearing device fitting on daily-life fatigue - Holman, Jack A. (2020)
For many years, anecdotal evidence has suggested that people with hearing loss experience disproportionate levels of fatigue. The aetiology of fatigue associated with hearing loss was also thought to be uncomplicated. The basic energy depletion theory states that decreased audibility and fidelity result in an increased need for listening effort to maintain conversational performance. This, in turn, drains finite cognitive resources and results in increased fatigue. By the same logic, hearing device fitting should decrease fatigue by improving audibility and reducing the need for listening effort. However, recent research has not entirely supported this reasoning. Moreover, issues pertaining to the conceptualisation and measurement of fatigue have complicated efforts to measure its effects. Therefore, the research presented here was conducted to investigate the impact of hearing loss and hearing aid fitting on daily-life fatigue. Daily-life fatigue includes transient and long-term fatigue, and is contingent on the activities undertaken in everyday life.